Komunikasi Efektif Gaya Ceramah Ustadz Abdul Somad (UAS) Versus Adi Hidayat (UAH) - Nisa, Pia Khoirotun; Misnan, Misnan; Murodi, Murodi; Subhan, Arief (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
This study aims to show the effectiveness of the communication styles of Ustadz Abdul Somad (UAS) and Ustadz Adi Hidayat (UAH) through the lens of Aristotle’s persuasion theory, as well as to compare both based on the concepts of ethos, pathos, and logos. Adopting a constructivist paradigm, the study employs a communication and sermon science approach, utilizing a case study method. Data was collected through a review of digital media documentation and analyzed inductively using a thematic approach, including data coding, theme identification, and narrative construction. The findings reveal that UAS is more straightforward and simple in terms of logos in delivering its message, while UAH adopts a more analytical and comprehensive approach. Regarding pathos, UAS engages the audience emotionally through humor and light-hearted stories, while UAH encourages deeper reflection with real-life examples. Regarding ethos, both Ustadz holds high credibility, with UAS being perceived as more approachable, while UAH is seen as more academic. UAS’s communication style is more effective for a broad audience, utilizing an interactive and simple approach. In contrast, UAH’s style is more effective for an audience seeking in-depth understanding through an academic and introspective approach.